Two-component inorganic grouting material as well as preparation method and application thereof
Through the design of two-component inorganic grouting materials, the use of specific additives to maintain fluidity and quickly condense, the problems of blockage and insufficient strength of traditional grouting materials are solved, and efficient mine reinforcement and water blocking effects are achieved.
Patent Information
- Application Number
- CN202310699113.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
Traditional grouting materials cannot stay in the conveying pipeline for a long time, which is prone to block the pipeline, and the strength of the grouting body is insufficient, so it cannot effectively reinforce the broken surrounding rock, and there is slurry leakage.
Two-component inorganic grouting materials are used. Components A and components B contain aluminate cement, mineral blends, retarders, water reducing agents, viscosity reducing agents and thickeners, which synergistically act through specific additives. Maintain fluidity and quickly condense after mixing to achieve high final coagulation strength.
The long-term fluidity and rapid condensation of components A and B in the pipeline are achieved, the fluidity and strength of grouting materials are improved, and the problems of blockage and insufficient strength of traditional materials are solved. It is suitable for mine backfill and reinforcement.
Abstract
Description
Technical Field
[0001] The invention relates to the field of grouting materials, and in particular to a two-component inorganic grouting material and a preparation method and application thereof. Background Art
[0002] With the rapid development of industry, our demand for resources has also increased dramatically. Coal resources still occupy an important position in my country's energy structure, so mining operations gradually extend to deeper areas, and the pressure on the surrounding rock of the tunnels also increases. Conventional support methods cannot meet the requirements of deep mining operations, and the stability and safety issues of the tunnels have become increasingly prominent. Grouting reinforcement technology greatly improves the strength and self-bearing capacity of the surrounding rock, and can effectively control weak surrounding rock and maintain tunnel stability.
[0003] Traditional grouting materials generally have the problem that the slurry cannot stay in the conveying pipeline for a long time, which is easy to block the pipeline and seriously affect the construction period. After the conveying stops, a large amount of water is needed to flush the excess slurry in the pipeline, otherwise the slurry will block the pipeline after hardening, affecting the next construction. There are still gaps in the grouting body after grouting, and the overall strength of the grouting body does not meet the requirements, and it is impossible to effectively reinforce the broken surrounding rock; after the slurry is injected into the surrounding rock, it is easy to leak, and the broken surrounding rock cannot be effectively reinforced.
[0004] Patent application CN202111303003.9 discloses an inorganic reinforcement material for mining, including the following components by mass percentage: 21.9% to 27.3% water, 37.5% to 38.3% sulphoaluminate cement, 1.2% to 2.0% soda ash, 3.9% to 5.9% lime, 19.5% to 26.6% gypsum, 7.8% to 11.7% stone powder, and 0.8% to 1.2% water reducer. In this patent document, all components are added together without distinguishing between component A and component B. There is a problem of easy coagulation after mixing, and it is impossible to stay in the pipeline for a long time; and the patent document uses sulphoaluminate cement and gypsum as raw materials, and it is impossible to obtain a higher strength inorganic grouting material.
[0005] Therefore, there is an urgent need for an inorganic grouting material that can stay in the pipeline for a long time and enable the grouting body to obtain higher strength. Summary of the invention
[0006] In the two-component inorganic grouting material provided by the present invention, component A and component B can respectively maintain good fluidity for a long time, and can quickly solidify after component A and component B are mixed, so that the obtained grouting material can achieve a higher final setting strength.
[0007] To achieve the above purpose, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a two-component inorganic grouting material, comprising component A and component B, wherein the component A comprises a solid component A and water in a mass ratio of 1: (0.2-0.5), and the solid component A comprises 100 parts by weight of aluminate cement, 0.01-10 parts by weight of mineral admixture, 0.1-6 parts by weight of retarder, 0.01-5 parts by weight of water reducer, 0.005-0.1 parts by weight of viscosity reducer, and 0.005-0.1 parts by weight of thickener;
[0009] The B component includes a B solid component and water in a mass ratio of 1: (0.35-0.7), wherein the B solid component includes 100 parts by weight of a calcium-containing mineral, 0.01-2 parts by weight of a retarder, 0.01-2 parts by weight of a water reducer, 0.005-0.1 parts by weight of a viscosity reducer, and 0.005-0.1 parts by weight of a thickener;
[0010] The weight ratio of the component A to the component B is 1:(0.5-2).
[0011] By adding specific amounts of mineral admixtures, retarders, water reducers, viscosity reducers and thickeners, the above-mentioned additives work synergistically to enable component A to maintain excellent long-term fluidity, with an initial fluidity of component A ≥360mm and a fluidity of ≥340mm after 20 hours; by adding specific amounts of retarders, water reducers, viscosity reducers and thickeners, the above-mentioned additives work synergistically to enable component B to also maintain excellent long-term fluidity, with an initial fluidity of component B ≥350mm and a fluidity of ≥340mm after 20 hours; on this basis, through the combined action of the aluminate cement in component A and the calcium-containing mineral in component B, and adjusting the mass ratio of the solid components and water in components A and B, rapid setting (initial setting time ≤20min, final setting time ≤30min) can be achieved after mixing, and early strength (0.5h) can be obtained.
[0012] The mineral admixture is made by ultrafine grinding process (median diameter of the mineral admixture is ≤45 μm). Adding a small amount of mineral admixture to component A is beneficial to improving the fluidity of component A and can also effectively control the slump loss of the mixed slurry. In some preferred embodiments, the mineral admixture is selected from one or more of fly ash, blast furnace slag, steel slag powder, silica fume and zeolite powder.
[0013] The calcium oxide in the calcium-containing mineral in the B component helps the hydration of the aluminate cement in the A component after the A component and the B component are mixed, thereby increasing the early strength of the grouting material after solidification, and the calcium oxide reacts with water to produce calcium hydroxide, providing an alkaline environment. In some preferred embodiments, in the B component, the calcium-containing mineral includes calcium oxide; preferably, the calcium-containing mineral also includes silicon oxide and aluminum oxide. Aluminum oxide and silicon oxide will undergo gelling reaction in an alkaline environment, filling the gaps of cement hydration products, thereby further improving the strength of the grouting material after solidification.
[0014] In some preferred embodiments, the calcium-containing mineral further includes sulfur oxide. Calcium oxide in the calcium-containing mineral reacts with water to produce calcium hydroxide, which further reacts with sulfur oxide to produce calcium sulfate, which further promotes the hydration of aluminate cement.
[0015] In some preferred embodiments, the calcium-containing mineral further comprises other oxides, and the other oxides are selected from sodium oxide, potassium oxide, magnesium oxide or iron oxide. The above oxide components can absorb water and water reducing agent and make them evenly distributed in component B, thereby improving the fluidity of component B before mixing.
[0016] In some preferred embodiments, based on the total mass of the calcium-containing mineral in the B component, the content of calcium oxide is 25 ~ The content of aluminum oxide is 10% to 15%, the content of sulfur oxide is 5% to 10%, and the content of other oxides is 5% to 40%.
[0017] In some preferred embodiments, the retarder in component A is an organic acid containing a carboxylate group, preferably tartaric acid. By adding the retarder to component A, the fluidity and setting time of the slurry can be further regulated.
[0018] In some preferred embodiments, citric acid or glucose is added as a retarder to component B to improve the fluidity of the slurry and prolong the setting time. The inventors of the present invention have found that since the calcium-containing mineral contains a large amount of CaO, adding tartaric acid as a retarder to component B will cause component B to harden quickly, while adding citric acid or glucose will not cause the above phenomenon.
[0019] By adding a retarder and a water reducer to component A, the fluidity of component A can be further improved and the setting time of component A can be prolonged, but stratification and bottom grabbing are prone to occur, which is not conducive to pipeline transportation. Therefore, in some preferred embodiments, by adding hydroxypropyl methylcellulose with a viscosity ≥ 10,000 as a thickener and sodium dodecylbenzene sulfonate as a viscosity reducer, the viscosity of the slurry can be greatly improved while the fluidity is improved, so that the cement particles will not sink and cause stratification and bottom grabbing.
[0020] The slurry obtained by mixing the calcium-containing mineral in the B component with water is thixotropic, and is very hard when stirred. When stirring is stopped, the slurry becomes very thin, that is, it becomes thicker and harder under stress, which is not conducive to transportation. At the same time, considering that the calcium-containing mineral in the B component has a certain viscosity after being dissolved in water, hydroxypropyl methylcellulose with a viscosity of <10000 is added as a thickener, and sodium dodecylbenzene sulfonate is added as a viscosity reducer to effectively control the slurry state of the B component so that the B component meets the transportation requirements.
[0021] In some preferred embodiments, the water reducer is a polycarboxylic acid powder water reducer; preferably, the water reducer is Sika 540P. Sika 540P has good compatibility with aluminate cement, and thus has a good water reducing effect.
[0022] The second aspect of the present invention provides a method for preparing a two-component inorganic grouting material, comprising: mixing aluminate cement, mineral admixture, retarder, water reducer, viscosity reducer, thickener and water in proportion to obtain component A; adding calcium-containing mineral, retarder, water reducer, viscosity reducer, thickener and water in proportion to mix to obtain component B; mixing the component A with the component B to obtain a two-component inorganic grouting material.
[0023] In some preferred embodiments, the initial fluidity of component A is ≥360 mm, and the fluidity after 20 hours is ≥340 mm, the initial fluidity of component B is ≥350 mm, and the fluidity after 20 hours is ≥340 mm, the initial setting time after mixing component A and component B is ≤20 min, the final setting time is ≤30 min, and the 0.5 h compressive strength is ≥1 MPa.
[0024] The third aspect of the present invention provides the use of the two-component inorganic grouting material as described above or the two-component inorganic grouting material prepared by the preparation method as described above in water blocking and / or reinforcement.
[0025] The technical solution provided by the present invention has the following beneficial effects:
[0026] (1) By adding mineral admixtures, retarders, water reducers, viscosity reducers and thickeners to component A, the above additives work synergistically, so that component A can maintain excellent long-term fluidity, and the initial fluidity of component A is ≥360mm, and the fluidity after 20 hours is ≥340mm; by adding retarders, water reducers, viscosity reducers and thickeners, the above additives work synergistically, so that component B can also maintain excellent long-term fluidity, and the initial fluidity of component B is ≥350mm, and the fluidity after 20 hours is ≥340mm;
[0027] (2) Through the interaction between aluminate cement and calcium-containing minerals, and by adjusting the mass ratio of solid components to water in components A and B, components A and B can be mixed to achieve rapid setting, with an initial setting time of ≤20 min, a final setting time of ≤30 min, and strength within 0.5 h;
[0028] (3) The two-component inorganic grouting material has a wide range of uses, and can be used for mine backfill materials, grouting reinforcement materials, mine water plugging materials, etc., and the preparation process is simple, and it has good practicality and industrial feasibility. DETAILED DESCRIPTION
[0029] The present invention is further described below by means of specific embodiments. The embodiments of the present invention are only used as illustrations of the present invention and do not mean that the scope of the present invention is limited thereto.
[0030] instrument:
[0031] Pressure testing machine: TYE-300D cement mortar flexural and compression testing machine
[0032] Water seepage rate test: SY-2 concrete pressure water seepage meter
[0033] Example 1
[0034] Example 1-1
[0035] 100 g of aluminate cement, 5 g of fly ash, 1 g of tartaric acid, 1.5 g of Sika 540P, 0.01 g of sodium dodecylbenzene sulfonate, and 0.01 g of hydroxypropyl methylcellulose were mixed, and 38 g of water was added to obtain a component A slurry material.
[0036] The initial fluidity of the A component slurry material is 360mm, and the 20h fluidity is 340mm. There is no stratification and bottom grabbing after 20h.
[0037] Example 1-2
[0038] 100 g of aluminate cement, 5 g of S95 mineral powder, 1 g of tartaric acid, 2 g of Sika 540P, 0.01 g of sodium dodecylbenzene sulfonate, and 0.01 g of hydroxypropyl methylcellulose were mixed, and 38 g of water was added to obtain a component A slurry material.
[0039] The initial fluidity of the A component slurry material is 370mm, and the 20h fluidity is 360mm. There is no stratification and bottom grabbing after 20h.
[0040] Examples 1-3
[0041] 100 g of aluminate cement, 10 g of fly ash, 1 g of tartaric acid, 3 g of Sika 540P, 0.03 g of sodium dodecylbenzene sulfonate, and 0.03 g of hydroxypropyl methylcellulose were added for mixing, and 48 g of water was added to obtain a component A slurry material.
[0042] The initial fluidity of the A component slurry material is 390mm, and the 20h fluidity is 380mm. There is no stratification and bottom grabbing after 20h.
[0043] Comparative Example 1-1
[0044] 100 g of aluminate cement, 2 g of tartaric acid, and 0.5 g of Sika 540P were mixed, and 38 g of water was added to obtain a component A slurry material.
[0045] The initial fluidity of the A component slurry material was 210 mm, and it no longer expanded after 20 hours.
[0046] Comparative Example 1-2
[0047] 100 g of aluminate cement, 5 g of fly ash, 1 g of tartaric acid, and 1.5 g of Sika 540P were mixed, and 38 g of water was added to obtain a component A slurry material.
[0048] The initial fluidity of component A slurry material was 340 mm, and the fluidity after 20 hours was 330 mm. After 20 hours, stratification and water seepage occurred.
[0049] Comparative Examples 1-3
[0050] 100 g of aluminate cement, 5 g of fly ash, 1 g of tartaric acid, 1.5 g of Sika 540P, and 0.01 g of sodium dodecylbenzene sulfonate were mixed, and 38 g of water was added to obtain a component A slurry material.
[0051] The initial fluidity of the A component slurry material is 280mm, the 20h fluidity is 430mm, and there is bottom grabbing after 20h.
[0052] In Comparative Example 1-1, compared with Examples 1-1, 1-2 and 1-3, only a small amount of Sika 540P was added, and no mineral admixture, viscosity reducer and thickener were added. After 20 hours, the slurry material of component A no longer flowed. In Comparative Example 1-2, compared with Examples 1-1, 1-2 and 1-3, no viscosity reducer and thickener were added. After 20 hours, the slurry material of component A was stratified and exuded. In Comparative Example 1-3, compared with Examples 1-1, 1-2 and 1-3, no thickener was added. After 20 hours, the slurry material of component A had a bottom grip.
[0053] Example 2
[0054] Example 2-1
[0055] 100 g of calcium-containing mineral, 0.5 g of citric acid, 0.25 g of XIKA 540P, 0.01 g of hydroxypropyl methylcellulose, and 0.025 g of sodium dodecylbenzene sulfonate were mixed, and 53 g of water was added to obtain a B component slurry material.
[0056] Among them, based on the total mass of calcium-containing minerals: the content of calcium oxide is 40%, the content of silicon oxide is 30%, the content of aluminum oxide is 10%; the content of sulfur oxide is 5%; other oxides are 15%; among them, the content of sodium oxide is 10% and the content of magnesium oxide is 5%.
[0057] The initial fluidity of the B component slurry material is 350mm, and the 20h fluidity is 340mm. There is no water seepage and no stratification after 20h.
[0058] Example 2-2
[0059] 100 g of calcium-containing mineral, 1 g of citric acid, 0.5 g of XIKA 540P, 0.03 g of hydroxypropyl methylcellulose, and 0.05 g of sodium dodecylbenzene sulfonate were mixed, and 65 g of water was added to obtain a slurry material of component B. The composition of the calcium-containing mineral was the same as that of Example 2-1.
[0060] The initial fluidity of the B component slurry material is 370mm, and the 20h fluidity is 360mm. There is no water seepage and no stratification after 20h.
[0061] Example 2-3
[0062] 100 g of calcium-containing mineral, 2 g of glucose, 0.3 g of XIKA 540P, 0.01 g of hydroxypropyl methylcellulose, and 0.03 g of sodium dodecylbenzene sulfonate were mixed, and 60 g of water was added to obtain a slurry material of component B. The composition of the calcium-containing mineral was the same as that of Example 2-1.
[0063] The initial fluidity of the B component slurry material is 380mm, and the 20h fluidity is 370mm. There is no water seepage and no stratification after 20h.
[0064] Comparative Example 2-1
[0065] 100 g of calcium-containing mineral and 0.1 g of Sika 540P were mixed, and 53 g of water was added to obtain a slurry material of component B. The composition of the calcium-containing mineral was the same as that of Example 2-1.
[0066] The initial fluidity of the B component slurry material was 430 mm. After 20 hours, it had hardened and no longer flowed.
[0067] Comparative Example 2-2
[0068] 100 g of calcium-containing mineral, 1 g of citric acid, and 0.25 g of XIKA 540P were mixed, and 53 g of water was added to obtain a slurry material of component B. The composition of the calcium-containing mineral was the same as that of Example 2-1.
[0069] The initial fluidity of the B component slurry material was 240 mm, and it no longer expanded and had no stratification after 20 hours.
[0070] Comparative Examples 2-3
[0071] 100 g of calcium-containing mineral, 0.5 g of citric acid, and 0.25 g of XIKA 540P were mixed, and 53 g of water was added to obtain a slurry material of component B. The composition of the calcium-containing mineral was the same as that of Example 2-1.
[0072] The initial fluidity of the B component slurry material is 340mm, and the 20h fluidity is 300mm. After 20h, there is a small amount of water seepage and no stratification.
[0073] Comparative Examples 2-4
[0074] 100 g of calcium-containing mineral was mixed with 0.25 g of citric acid and 0.5 g of XIKA 540P while stirring, and then 53 g of water was added to obtain a slurry material of component B. The composition of the calcium-containing mineral was the same as that of Example 2-1.
[0075] The initial fluidity of the B component slurry material was 440 mm. After 20 hours, it stopped flowing, and stratification occurred, with the lower part completely hardened.
[0076] In Comparative Example 2-1, compared with Examples 2-1, 2-2, 2-3 and 2-4, no retarder, viscosity reducer and thickener were added, and the slurry material of component B no longer flowed after 20 hours. In Comparative Example 2-2, compared with Examples 2-1, 2-2, 2-3 and 2-4, no viscosity reducer and thickener were added and if relatively more retarder was added at the same time, and the stirring state was continuously maintained, the slurry material of component B hardened and no longer flowed after 20 hours due to thixotropy. In Comparative Example 2-3, compared with Examples 2-1, 2-2, 2-3 and 2-4, no viscosity reducer and thickener were added, and the slurry material of component B had a small amount of exudation after 20 hours, and no stratification. In Comparative Example 2-4, compared with Examples 2-1, 2-2, 2-3 and 2-4, no viscosity reducer and thickener were added and if relatively more water reducer was added at the same time, the slurry material of component B produced stratification after 20 hours, and the lower part was completely hardened.
[0077] Example 3
[0078] Example 3-1
[0079] 500 g of the A component slurry material obtained in Example 1-1 and 500 g of the B component slurry material obtained in Example 2-1 were fully mixed at a mass ratio of 1:1 to obtain a two-component inorganic grouting material.
[0080] The initial setting time of the two-component inorganic grouting material is 14 minutes, the final setting time is 15 minutes, the 0.5h compressive strength is 3.8MPa, and the 28d compressive strength is 47.6MPa.
[0081] Example 3-2
[0082] 400 g of the A component slurry material obtained in Example 1-1 and 600 g of the B component slurry material obtained in Example 2-1 were fully mixed at a mass ratio of 2:3 to obtain a two-component inorganic grouting material.
[0083] The initial setting time of the two-component inorganic grouting material is 8 minutes, the final setting time is 10 minutes, the 0.5h compressive strength is 12.6MPa, and the 28d compressive strength is 43.9MPa.
[0084] Example 3-3
[0085] 300 g of the A component slurry material obtained in Example 1-1 and 600 g of the B component slurry material obtained in Example 2-1 were fully mixed at a mass ratio of 1:2 to obtain a two-component inorganic grouting material.
[0086] The initial setting time of the two-component inorganic grouting material is 10 minutes, the final setting time is 12 minutes, the 0.5h compressive strength is 7.8MPa, and the 28d compressive strength is 36.9MPa.
[0087] Embodiment 3-4
[0088] 600 g of the A component slurry material obtained in Example 1-1 and 300 g of the B component slurry material obtained in Example 2-1 were fully mixed at a mass ratio of 2:1 to obtain a two-component inorganic grouting material.
[0089] The initial setting time of the two-component inorganic grouting material is 18 minutes, the final setting time is 20 minutes, the 0.5h compressive strength is 1.3MPa, and the 28d compressive strength is 41.9MPa.
[0090] Comparative Example 3-1
[0091] 600 g of the A component slurry material obtained in Example 1-1 and 200 g of the B component slurry material obtained in Example 2-1 were fully mixed at a mass ratio of 3:1 to obtain a two-component inorganic grouting material.
[0092] The initial setting time of the two-component inorganic grouting material is greater than 30 minutes, the compressive strength at 0.5 hours is 0 MPa, and the compressive strength at 28 days is 49.8 MPa.
[0093] Comparative Example 3-2
[0094] 200 g of the A component slurry material obtained in Example 1-1 and 600 g of the B component slurry material obtained in Example 2-1 were fully mixed at a mass ratio of 1:3 to obtain a two-component inorganic grouting material.
[0095] The initial setting time of the two-component inorganic grouting material is greater than 30 minutes, the compressive strength at 0.5 hours is 0 MPa, and the compressive strength at 28 days is 29.6 MPa.
[0096] Comparative Example 3-3
[0097] 400 g of the A component slurry material obtained in Example 3-2 and 600 g of the non-B component slurry material obtained by replacing the calcium-containing mineral in Example 3-2 with a calcium-free mineral are fully mixed in a mass ratio of 2:3 to obtain a two-component inorganic grouting material.
[0098] The total mass of calcium-free minerals is as follows: 50% silicon oxide, 20% aluminum oxide, 10% iron oxide, 8% sulfur oxide, and 12% potassium oxide.
[0099] The initial setting time of the two-component inorganic grouting material is greater than 30 minutes, the compressive strength at 0.5 hours is 0 MPa, and the compressive strength at 28 days is 34.2 MPa.
[0100] Comparative Examples 3-4
[0101] 400 g of the non-A component slurry material obtained by replacing the aluminate cement in Example 3-2 with sulphoaluminate cement and 600 g of the B component slurry material obtained in Example 3-2 were fully mixed in a mass ratio of 2:3 to obtain a two-component inorganic grouting material.
[0102] The initial setting time of the two-component inorganic grouting material is 21 minutes, the final setting time is 28 minutes, the 0.5h compressive strength is 0.5MPa, and the 28d compressive strength is 36.3MPa.
[0103] Compared with Examples 3-1, 3-2, 3-3 and 3-4, more component A is added in Comparative Example 3-1. After mixing, the mixture does not coagulate within 30 minutes, and the mixed material does not have compressive strength in a short time. In Comparative Example 3-2, more component B is added. After mixing, the mixture also does not coagulate within 30 minutes, and the mixed material does not have compressive strength in a short time. In Comparative Example 3-3, the calcium-containing mineral in component B is replaced with a calcium-free mineral. After mixing, the mixture also does not coagulate within 30 minutes, and the mixed material does not have compressive strength in a short time. In Comparative Example 3-4, the aluminate cement in component A is replaced with sulphoaluminate cement. The initial setting time is greater than 20 minutes, the 0.5h strength is lower than 1MPa, and the early strength characteristics are weaker than those of Examples 3-1, 3-2, 3-3 and 3-4.
[0104] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A two-component inorganic grouting material, It is characterized in that It comprises component A and component B, wherein the component A comprises solid component A and water in a mass ratio of 1:(0.2-0.5), and the solid component A comprises 100 parts by weight of aluminate cement, 0.01-10 parts by weight of mineral admixture, 0.1-6 parts by weight of retarder, 0.01-5 parts by weight of water reducer, 0.005-0.1 parts by weight of viscosity reducer, and 0.005-0.1 parts by weight of thickener; The B component includes a B solid component and water in a mass ratio of 1: (0.35-0.7), wherein the B solid component includes 100 parts by weight of a calcium-containing mineral, 0.01-2 parts by weight of a retarder, 0.01-2 parts by weight of a water reducer, 0.005-0.1 parts by weight of a viscosity reducer, and 0.005-0.1 parts by weight of a thickener; The mass ratio of the component A to the component B is 1:(0.5-2).
2. The two-component inorganic grouting material according to claim 1, It is characterized in that The mineral admixture is selected from one or more of fly ash, blast furnace slag, steel slag powder, silica fume and zeolite powder.
3. The two-component inorganic grouting material according to claim 1, It is characterized in that The calcium-containing mineral includes calcium oxide; Preferably, the calcium-containing mineral further comprises silicon oxide, aluminum oxide, sulfur oxide and other oxides, and the other oxides are selected from sodium oxide, potassium oxide, magnesium oxide or iron oxide; More preferably, based on the total mass of the calcium-containing mineral in the B component, the content of calcium oxide is 25-40%, the content of silicon oxide is 20-30%, the content of aluminum oxide is 10-15%, the content of sulfur oxide is 5-10%, and the content of other oxides is 5%-40%.
4. The two-component inorganic grouting material according to claim 1, It is characterized in that The retarder in the component A is an organic acid containing a carboxylate group, preferably tartaric acid; the retarder in the component B is citric acid or glucose.
5. The two-component inorganic grouting material according to claim 1, It is characterized in that The thickener in component A is hydroxypropyl methylcellulose with a viscosity of ≥10000; the thickener in component B is <10000 of Hydroxypropyl Methylcellulose.
6. The two-component inorganic grouting material according to claim 1, It is characterized in that The water reducer is a polycarboxylic acid powder water reducer; preferably, the water reducer is Sika 540P; The viscosity reducing agent is sodium dodecylbenzene sulfonate.
7. A method for preparing a two-component inorganic grouting material according to any one of claims 1 to 6, It is characterized in that include: Aluminate cement, mineral admixture, retarder, water reducer, viscosity reducer, thickener and water are mixed according to proportion to obtain component A; Add calcium-containing mineral, retarder, water reducer, viscosity reducer, thickener and water in proportion and mix to obtain component B; The component A and the component B are mixed to obtain a two-component inorganic grouting material.
8. The method for preparing the two-component inorganic grouting material according to claim 7, It is characterized in that The initial fluidity of the A component is ≥360 mm, and the fluidity after 20 hours is ≥340 mm. The initial fluidity of the B component is ≥350 mm, and the fluidity after 20 hours is ≥340 mm.
9. The method for preparing the two-component inorganic grouting material according to claim 7, It is characterized in that After the component A and the component B are mixed, the initial setting time is ≤20min, the final setting time is ≤30min, and the 0.5h compressive strength is ≥1MPa.
10. Use of the two-component inorganic grouting material according to any one of claims 1 to 6 or the two-component inorganic grouting material prepared by the preparation method according to any one of claims 7 to 9 in water blocking and / or reinforcement.
Citation Information
Cited By
Mining high-strength quick-setting cement grouting material and preparation method thereof
CN121021101A
A mine-used high-strength rapid-setting cement grouting material and a preparation method thereof
CN121021101B
